2013
DOI: 10.1249/mss.0b013e3182995349
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform Muscle Hypertrophy

Abstract: The results suggest that nonuniform muscle hypertrophy after training intervention is due to the region-specific muscle activation during the training session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
57
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(64 citation statements)
references
References 22 publications
4
57
0
3
Order By: Relevance
“…Studies have reported that changes in morphology (e.g., anatomical cross-sectional area, muscle thickness) and architecture (e.g., fascicle length, pennation angles) in response to resistance training occurs non-uniformly along the length of the muscle [10, 11]. This non-uniform muscle adaptation to resistance exercise is particular true for eccentric training [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that changes in morphology (e.g., anatomical cross-sectional area, muscle thickness) and architecture (e.g., fascicle length, pennation angles) in response to resistance training occurs non-uniformly along the length of the muscle [10, 11]. This non-uniform muscle adaptation to resistance exercise is particular true for eccentric training [12].…”
Section: Introductionmentioning
confidence: 99%
“…This non-uniform muscle adaptation to resistance exercise is particular true for eccentric training [12]. The non-uniform change in muscle morphology and architecture after a training intervention has been attributed to the region-specific muscle activation assessed by the transverse relaxation time (T 2 ) of functional magnetic resonance images (fMRI) during the training session [10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…Estudos têm associado uma elevada resposta da concentração de lactato sanguíneo com um aumento no recrutamento de unidades motoras rápidas 5,6 , e uma maior resposta hipertrófica 7 . Considerando que as fibras musculares recrutadas durante o treinamento de força estariam suscetíveis à adaptação 8,9 , protocolos que apresentam maior resposta eletromiográfica e concentração sanguínea de lactato teriam maior potencial para promover maiores aumentos na força e hipertrofia muscular 7,10 . A prescrição de um programa de treinamento de força na musculação deve considerar diferentes variáveis, sendo que a manipulação de uma destas variáveis, a duração da repetição, pode interferir na atividade eletromiográfica 4,11,12 e na concentração de lactato sanguíneo 7 .…”
Section: Introductionunclassified
“…Estudos têm associado uma elevada resposta da concentração de lactato sanguíneo com um aumento no recrutamento de unidades motoras rápidas 5,6 , e uma maior resposta hipertrófica 7 . Considerando que as fibras musculares recrutadas durante o treinamento de força estariam suscetíveis à adaptação 8,9 , …”
unclassified
“…Some of these studies have also measured the concentration of blood lactate (Eckhardt et al, 2011;Lacerda et al, 2016;Smilios et al, 2010;Takarada et al, 2000;Walker et al, 2011) because the augmented lactate response has been associated with an increased recruitment of fast-twitch motor units (Gladden, 2004;Moritani, Tanaka, Yoshida, Ishii, Yoshida, & Shindo, 1984). Given the expectation that the activated muscle fibers are those that adapt to training (Spiering et al, 2008;Wakahara, Fukutani, Kawakami, & Yanai, 2013), protocols which show higher electromyographic amplitude would present greater potential to promote increases in strength and muscle hypertrophy (Takarada et al;Watanabe, Madarame, Ogasawara, Nakazato, & Ishii, 2014).…”
Section: Introductionmentioning
confidence: 99%